2018
DOI: 10.1038/s41556-018-0132-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of transition zone and centriole proteins contributes to ciliary base diversity

Abstract: Cilia are evolutionarily conserved structures with many sensory and motility-related functions. The ciliary base, composed of the basal body and the transition zone, is critical for cilia assembly and function, but its contribution to cilia diversity remains unknown. Hence, we generated a high-resolution structural and biochemical atlas of the ciliary base of four functionally distinct neuronal and sperm cilia types within an organism, Drosophila melanogaster. We uncovered a common scaffold and diverse structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 73 publications
11
80
0
Order By: Relevance
“…We detected the peaks of the profiles and measured the angle (the distance in the profile plots) from each peak to its nearest neighbor to quantify the periodicity of the discrete ring patterns. Similar methods have been used successfully to analyze protein localization patterns in the ciliary transition zone or centriole distal appendages (Shi et al, 2017;Jana et al, 2018;Yang et al, 2018). The average angle between nearest-neighbor pairs was ∼60° (Fig.…”
Section: Stimulated Emission Depletion (Sted) Super-resolution Microsmentioning
confidence: 94%
“…We detected the peaks of the profiles and measured the angle (the distance in the profile plots) from each peak to its nearest neighbor to quantify the periodicity of the discrete ring patterns. Similar methods have been used successfully to analyze protein localization patterns in the ciliary transition zone or centriole distal appendages (Shi et al, 2017;Jana et al, 2018;Yang et al, 2018). The average angle between nearest-neighbor pairs was ∼60° (Fig.…”
Section: Stimulated Emission Depletion (Sted) Super-resolution Microsmentioning
confidence: 94%
“…We recently reported that SAS-6 not only constitutes the cartwheel structure but also is dynamically recruited to the spermatocyte BBs even after their cartwheel assembly. The later function of SAS-6 is required to elongate the BBs in the sperm cells (Jana et al, 2018). Here, our data suggest that pericentrin regulates the centriole length and stability by recruiting a part of the dynamic pool of SAS-6 to the centriole/BB.…”
Section: Implications Of Centriole Biogenesis and Elongationmentioning
confidence: 53%
“…SAS-6 is required for centriole biogenesis and recently implicated in centriole elongation (Hilbert et al, 2016;Jana et al, 2018). Therefore, we wondered in addition to STIL/Ana2 if pericentrin is indeed required for SAS-6 recruitment to the centriole and thereby its assembly and maturation in a multicellular organism, such as Drosophila.…”
Section: Drosophila Pericentrin Is Required For Sas-6 Recruitment Andmentioning
confidence: 99%
“…We detected the peaks of the profiles and measured the angle (the distance in the profile plots) from each peak to its nearest neighbor to quantify the periodicity of the discrete ring patterns. Similar methods have been used successfully to analyze protein localization patterns in the ciliary transition zone or centriole distal appendages (Jana et al, 2018; Shi et al, 2017; Yang et al, 2018). The average angles between nearest-neighbor pairs were approximately 60° (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%